Guided bone regeneration with plasma rich in fibrin in the treatment of periapical cyst: a clinical case report - Viera Mena, Kemberly Gabriela (2022)
Cysts are pathological cavities with liquid, semi-liquid, solid or gaseous content, lined with epithelium on the inside and by connective tissue on the outside. The peri-apical cyst is a common inflammatory lesion of the jaws, which upon reaching a significant size, retention or even the displacement of adjacent teeth, is derived from the remains of Malassez. A case was presented of a patient who came to the dental office, asymptomatic with the presence of leaking restorations. The clinical examination revealed soft palatal tissue without bone support at the level of pieces # 11 and # 12; radiographically, a hypodense, well-defined radiolucent image was evidenced, including vestibular and palatal tables, total palatal bone lysis and mucosal involvement. The lesion was surgically treated with apicoectomy, bone regeneration, and fibrin-rich plasma. In the postoperative control, an adequate healing process and absence of symptoms were observed.